Enhancing Fifth-Grade Students’ Understanding of the Human Digestive System through Interactive Science Media - Ria Juhariyani; Sarwanto; Roemintoyo (Universitas Pendidikan Ganesha, 2026)
The lack of optimal use of learning media in the classroom is one of the factors contributing to low science learning outcomes among elementary school students, particularly in learning the human digestive system. This study aims to explore the need for SiCerMa interactive media to support science learning on the human digestive system. The participants of this study involved elementary school teachers and fifth-grade students. The research employed a qualitative descriptive approach using the ADDIE development model with a focus on needs analysis. Data were collected through observation, document study, interviews, and questionnaires, while data analysis followed the interactive analysis model of Miles and Huberman. The findings indicate that students experience difficulties in understanding the human digestive system when learning relies on conventional media, and both teachers and students express a strong need for interactive science media. Interactive SiCerMa media integrated with problem-based learning is considered capable of supporting students’ conceptual understanding and learning engagement. The study concludes that concrete, interesting, and interactive learning media are essential to facilitate a better understanding of the human digestive system in elementary science learning.